2008
DOI: 10.1111/j.1467-9590.2007.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Shortest Queue Version of the Erlang Loss Model

Abstract: We consider two parallel M/M/N/N queues. Thus there are N servers in each queue and no waiting line(s). The network is fed by a single Poisson arrival stream of rate λ, and the 2N servers are identical exponential servers working at rate µ. A new arrival is routed to the queue with the smaller number of occupied servers. If both have the same occupancy then the arrival is routed randomly, with the probability of joining either queue being 1/2. This model may be viewed as the shortest queue version of the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There exists an extensive literature on dispatching policies and their optimality [9,26,27,35,36,37,42,46]. Among the dispatching policies, the join-the-shortest-queue (JSQ) policy has received considerable attention [5,6,10,19,20,23,24,28,30,44,45]. The JSQ policy in some scenarios has been proven to be the optimal policy; on the one hand it minimizes the customers mean waiting time [25] and on the other hand it stochastically maximizes the number of customers served by time t, t > 0 [43].…”
Section: Introductionmentioning
confidence: 99%
“…There exists an extensive literature on dispatching policies and their optimality [9,26,27,35,36,37,42,46]. Among the dispatching policies, the join-the-shortest-queue (JSQ) policy has received considerable attention [5,6,10,19,20,23,24,28,30,44,45]. The JSQ policy in some scenarios has been proven to be the optimal policy; on the one hand it minimizes the customers mean waiting time [25] and on the other hand it stochastically maximizes the number of customers served by time t, t > 0 [43].…”
Section: Introductionmentioning
confidence: 99%
“…and we also note that the expressions in Theorem 1 are consistent with (22). We will show that the asymptotics are quite different whether…”
Section: Theoremmentioning
confidence: 51%
“…In addition to this model being interesting on its own, many variants of shortest queue problems, such as ones with multiple servers and finite capacities, can be asymptotically reduced to LQ models of the type considered here (see [22,23]). For example, in [23] we showed that the finite capacity version of the standard symmetric SQ model (analyzed in [4,5]), where 𝑁 1 , 𝑁 2 ⩽ 𝐾 and 𝐾 is the capacity, asymptotically reduces to the symmetric LQ model in [1], if we consider the process (𝐾 − 𝑁 1 , 𝐾 − 𝑁 2 ), which measures the number of spots available in the two waiting rooms.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach to the M/M/n/n can be found in [8], where Yao & Knessl outlined two parallel M/M/n/n queues with n servers in each queue and no waiting lines. If both have the same occupancy, then the arrival is routed to any of them.…”
Section: Erlang-loss Systemmentioning
confidence: 99%